The Use of Google Classroom Application for Writing and Speaking in English Education Class - Paskalina Widiastuti Ratnaningsih (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2019)
The development of application in smartphone makes people use it in the process of teaching and learning activities. This research aims to discover students’ lived experience of using Google Classroom application as the media for submitting English assignments in the form of writing and speaking. The method used in this research was hermeneutic-phenomenology study. It focuses on description and interpretation of lived experience. The instruments used are in-depth interview, observation, and document review. The findings are distributed into empirical themes and transcendent themes. Based on the research, Google Classroom enhances writing and speaking skills in the form of assignments.